Hypersensitivity reaction to ofloxacin: A case report - Neki, N S (Journal of Chitwan Medical College, 2017)
Adverse drug reactions(ADRs) are noxious and unintended occurring in doses routinly used for diagnosis, treatment, prophylaxis of disease or for modification of physiological functions. Skin is the most commonly involved organ followed by GIT system although ADRS may involve any system. Ofloxacin is a quinolone antibiotic. It is considered as second-generation fluoroquinolone. It is effective for treatment of a wide variety of infectious diseases acting against both Gram-positive and Gram-negative bacteria. We present a case of hypersensitivity reaction to oral ofloxacin. Being rarity we thought of reporting this case.